Język rosyjski w Polsce — fakty i mity - Figarski, Władysław (Przegląd Rusycystyczny, 2008)
THE RUSSIAN LANGUAGE IN POLAND — THE FACTS AND THE MYTHS Summary Seeing through the lens of Poles’ perception of Russia and Russians over centuries, looking through the lens of Poland’s and Poles’ experience of relations with this great country, the author undertakes an analysis of a number of factors that have determined Poles’ attitudes towards the Russian language as a school subject. Some facts bearing on the attitudes are endorsed as true or approximating the truth, while others are exposed as myths, fi ction at odds with truth, often not even pretending to be true. It is emphasised, inter alia, that the Russian language in Poland has always been burdened with political overtones, most so during the period of partitions and in the years 1945–1989. This has had catastrophic consequences for the attitude of Poles towards the actual teaching and learning of the language of Pushkin in our country. However, the author posits that there are grounds for a change of the attitude to the Russian language and its place among other foreign languages taught at Polish schools, in the spirit of broadly-defi ned collaboration and tolerance, including language tolerance, in line with changes taking place across the civilised world. РУССКИЙ ЯЗЫК В ПОЛЬШЕ — ФАКТЫ И МИФЫ Резюме Глядя сквозь призму многовековой истории польско-российских взаимоотношений, автор статьи анализирует целый ряд факторов, повлиявших на отношение поляков к русскому языку как школьному предмету. Одни из них автор считает правдивыми или в некоторой степени приближенными к правде, в то время как другие рассматривает как мифы, которые далеки от правды, а иногда даже лишены и доли правды. Автор также подчёркивает, что на русский язык в Польше всегда оказывала огромное влияние политика двух государств, достигшяя своего апогея в годы Раздела Речи Посполитой, а также в период 1945–1989 гг. Последствия такой ситуации катастрофически повлияли как на процесс обучения русскому языку, так и на отношение поляков к языку Пушкина в нашей стране. Однако, несмотря на это, автор статьи выражает мнение, что существуют все основания предполагать, что отношение поляков к русскому языку коренным образом изменится, что русский язык займёт достойное место среди других иностранных языков в польских школах, что обучение ему будет проходить в атмосфере сотрудничества, взаимопонимания и толерантности, в том числе языковой толерантности, к чему в настоящее время стремится весь цивилизованный мир.